Retrieving Against the Flow: Incoherence Between Optic Flow and Movement Direction Has Little Effect on Memory for Order - Díez, Emiliano; Díez-Álamo, Antonio M.; Wojcik, Dominika Z.; Glenberg, Arthur M.; Fernandez, Angel (Frontiers in Human Neuroscience, 2018)
Research from multiple domains, including the investigation of mnemonics, cognitive development, and neuroscience suggest a link between self-locomotion and memory. In two free recall experiments with adults, we looked for a link between a) memory, and b) the coherence of movement and optic flow. In both experiments, participants heard lists of words while on a treadmill and wearing a virtual reality (VR) headset. In the first experiment, the VR scene and treadmill were stationary during encoding. During retrieval, all participants walked forward, but the VR scene was stationary, moved forward, or moved backwards. In the second experiment, during encoding all participants walked forward and viewed a forward-moving VR scene. During retrieval, all participants continued to walk forward but the VR scene was stationary, forward-moving, or backward-moving. In neither experiment was there a significant difference in the amount recalled, or output order strategies, attributable to differences in movement conditions.